PENGARUH KOMUNIKASI, MOTIVASI DAN ETOS KERJA TERHADAP KINERJA PEGAWAI KOORDINATOR UNIT PELAKSANA TEKNIS DINAS PENDAPATAN PROVINSI JAWA TIMUR DI PROBOLINGGO - Hastuti, Sri; Sularso, R. Andi; Komariyah, Siti (Universitas Jember, 2013)
This study was built with the aim to determine the relationship between communication patterns, with a work ethic as an intervening variable, communication on performance. Similarly, the relationship between the motivation to employee performance, motivation towards work ethic adan performance to performance. The study was conducted at the office of the Technical Unit Coordinator Department of Revenue in Probolinggo, East Java Province. As the sample is all employees in the institution totaling 150 respondents. The model used is a Structural Equation Model. Results of the study concluded that: (1) Communication Skills significant effect on work ethic. (2) Motivation employee owned significant effect on work ethic. (3) Work ethic significant effect on employee performance. (4) Communication significant effect on performance, and (5) Motivation significant effect on performance. Keywords : Communication, Motivation, Work ethic and employee performance